The administration of Syariah Courts in Malaysia, 1957–2009 - Wan Muhammad, Ramizah (Taylor & Francis Group, 2012)
This article analyses the development of the administration of Syariah Courts in Malaysia from the pre-colonial to the post-independence periods. The status of Islam as the official religion during the Malacca Sultanate and the application of Islamic law throughout the administration during that period are agreed upon by most historians. The structure of courts consisting of subordinate and superior levels with the Sultan as the head of the judiciary shows the existence of an organized structure which recognized natural justice as one of the rules of law. After Merdeka (independence), the restructuring and restoring of Syariah Courts in Malaysia took more than 40 years. Subsequently, the current Syariah Court acts and state enactments have been amended and improved to bring them into line with the policy of the government, current situations, and legal pluralism in Malaysia. The process of reform of the Syariah Court was slow, but Muslims in Malaysia handled the matter with tolerance, perseverance, and patience, and, most importantly, without jeopardizing the peace and harmony which is the hallmark of Malaysia as a nation.